Ionospheric peak height at the magnetic equator: Comparison between ionosonde measurements and IRI. Issue 2 (15th July 2017) - Maruyama, Takashi; Ma, Guanyi; Tsugawa, Takuya; Supnithi, Pornchai; Komolmis, Tharadol
Abstract: The ionospheric peak height in the F layer (hmF2) varies with not only thermospheric conditions but also dynamic processes in the upper atmosphere. At mid-latitudes, the field-aligned diffusion and recombination loss determine the hmF2 in the absence of applied vertical drift. Vertical drifts displace the hmF2 to a new equilibrium position in conjunction with the field-aligned redistribution of the plasma. In the vicinity of the magnetic equator, however, the equilibrium state would be different from low and mid-latitudes because the direct vertical coupling of plasma through the diffusion process is not allowed. Thus the behavior of hmF2 cannot be simply an extrapolation of that at low latitudes. In this paper, ionosonde measurements of the hmF2 near the magnetic equator and off-equatorial latitudes are compared with the IRI output.